A CFD-based study of twin-screw expander performance and inlet structure optimization. Issue 1 (1st March 2023) - Lin, Shuai
Abstract: Twin-screw expanders are widely used for small to medium-sized organic Rankine cycle (ORC) power generation. In order to improve the performance of twin-screw expanders in ORC, this study aims to improve the inlet efficiency and reduce the inlet pressure loss by changing the geometry of the inlet and shell. The CFD transient simulation is used to study the pressure, gas flow conditions and other parameters in the working chamber that are not easily obtained through experiments. The effects of improved size, speed, pressure ratio and internal volume ratio on the performance of the expander are analyzed based on the results. The results show that for the three expanders with different internal volume ratios, the optimized expander power and filling factor increases by 2%-14%. Isentropic efficiency of the expander reaches a maximum value of 0.73 when the pressure ratio is slightly greater than the internal volume ratio.